Pengaruh Karakteristik Sosial Ekonomi terhadap Strategi Coping Keluarga Pasca Gempa dan Tsunami di Nanggroe Aceh Darussalam - Siti Maryam (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
In the end of December 2004, earthquake and tsunami disaster attacked Nanggroe Aceh Darussalam Province and North Sumatera. The disaster caused : (a) great number of huge human victims; (b) the paralyzed of basic services; (c) basic infra structure disfunction; as well as (d) the destroy of social and economic system. The objectives of this research is to analyze the coping strategies of families after earthquake and tsunami disaster in Nanggroe Aceh Darussalam province. This research used cross-sectional design study, it’s was performed since May 2006 in Kuta Alam and Meuraxa sub districts. Number of samples were 138 families, which consist of 103 intact families, 20 widower families and 15 widow families. Sampling technique used proportional random sampling. Then, data was taken by using questionnaire.. Meanwhile, both coping problem-based strategy (44.2%) and emotion-based strategy (18.1%) of families were belonged into high level. Caracteristic economy social coping influence focus to problem is the health problem, social support and family tipology although caracteristic economy social also to influence strategy coping focus to emotion is personality, the age of head family, the sum members of family and suppot social.Keywords: coping strategies, family, caracteristic ecnomy social